Development of Articulate Storyline Interactive Media on Colloid Material to Improve Students’ Visual Abilities - Putri Dwi Anugrahani; Kharisma Kholidah Destafia; Rizky Alicia Miranti; Fahma Sairil Ulumil Khoiriyah; Kusumawati Dwiningsih; Maharani Agustina Arivi (JIPI (Jurnal IPA & Pembelajaran IPA), 2025)
Learning chemistry on abstract colloid material often causes difficulties, so interactive media such as articulate storyline is needed to visualize concepts and improve student understanding. The purpose of this study is to ascertain whether articulate storyline interactive learning materials can enhance students' visual abilities of colloid content. Research and development (R&D) using the ADDIE model was the research methodology employed. The average construct validity and content validity of the developed media were 94.84 and 98.18 percent, respectively, indicating that the media were suitable for use as learning tools.  The practicality of the media received an average practicality percentage of 75, which was considered practical and classified as good.  Based on the Wilcoxon test results, the effectiveness of the media was 0.000 (sig < 0.05).  In addition, students' visual abilities increased by an average of 0.44, falling into the medium category, based on the N-gain test results. Therefore, the developed learning media proved to be valid, practical, and effective in supporting chemistry learning and improving students' visual abilities